2019
DOI: 10.1103/physreve.99.051301
|View full text |Cite
|
Sign up to set email alerts
|

Application of atomic stress to compute heat flux via molecular dynamics for systems with many-body interactions

Abstract: Although the computation of heat flux and thermal conductivity either via Fourier's law or the Green-Kubo relation has become a common task in molecular dynamics simulation, contributions of three-body and larger many-body interactions have always proved problematic to compute. In recent years, due to the success when applying to pressure tensor computation, atomic stress approximation has been widely used to calculate heat flux, where the LAMMPS molecular dynamics package is the most prominent propagator. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 57 publications
5
68
1
Order By: Relevance
“…The simulations are then run for 20 ns, with the data taken within the last 10 ns being used to extract the heat transport properties, e.g., the temperature and heat flux. Although it has recently been shown that LAMMPS might incorrectly implement the heat flux formula in some cases [48,49], it is accurate for crystalline silicon [50]. The heat flux values in the sample are also close to those obtained by energy conservation [30] in our cases.…”
Section: Nemd Simulationssupporting
confidence: 81%
“…The simulations are then run for 20 ns, with the data taken within the last 10 ns being used to extract the heat transport properties, e.g., the temperature and heat flux. Although it has recently been shown that LAMMPS might incorrectly implement the heat flux formula in some cases [48,49], it is accurate for crystalline silicon [50]. The heat flux values in the sample are also close to those obtained by energy conservation [30] in our cases.…”
Section: Nemd Simulationssupporting
confidence: 81%
“…From the literature results [29,35], it is known that the optimized Tersoff potential gives higher thermal conductivity for SWCNTs than both generations of the Brenner potential. The second difference comes from the fact that some previous works [16,17,20] used the LAMMPS package [39], which has an incorrect implementation of the heat current for many-body potentials [35,[40][41][42]. This incorrect heat current also has an overall effect of underestimating the thermal conductivity of a low-dimensional material described by a many-body potential [35].…”
Section: Results From Emd Simulationsmentioning
confidence: 99%
“…It is important to note that both EMD methods require the heat flux vector J for computing thermal conductivities [73]. As shown in the recent studies by Surbyls et al [85] and Boone et al [86], the computation of J in molecular simulation packages such as LAMMPS can be erroneous for molecular systems having angles, torsions, dihedrals, and improper dihedrals, producing unphysical values. In fact, our preliminary thermal conductivity computations for reline using the Einstein method (OCTP plugin in LAMMPS [84]) yielded values which were almost an order of magnitude higher than the respective experiments.…”
Section: Müller-plathe (Mp) Methods For Computing Thermal Conductivitiesmentioning
confidence: 99%